PENDIDIKAN AGAMA ISLAM DALAM KELUARGA TERHADAP KEDISIPLINAN BERAGAMA SISWA MTS NEGERI 3 SAMBAS - Bustami (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2022)
This research aims to; to find out and analyze the effect of Islamic religious education in the family on the religious discipline of the students of MTs Negeri 3 Sambas. This research is descriptive quantitative research with causal associative research (cause and effect). The population with the research subject is students, totaling 89 students. Data collection by questionnaire method. The results showed that: (1) there was an influence of Islamic religious education in the family on religious discipline with a significance value of 0.00 and a magnitude of 0.619 (61.90%). The implications of the findings of this study are collaboration between schools and families in fostering religious discipline in order to realize the personality of students who are disciplined.